2018
DOI: 10.1038/s41598-018-30112-6
|View full text |Cite
|
Sign up to set email alerts
|

A 200-year annually laminated stalagmite record of precipitation seasonality in southeastern China and its linkages to ENSO and PDO

Abstract: In southeastern China (SEC), the precipitation amount produced by the East Asian summer monsoon (EASM) is almost equivalent to that during the non-summer monsoon (NSM) period, both of them significantly affecting agriculture and socioeconomy. Here, we present a seasonally-resolved stalagmite δ18O record (δ18Os) for the interval 1810–2009 AD from E’mei cave, Jiangxi Province, SEC. The comparison between δ18Os and instrumental data indicates that the δ18Os variability is primarily controlled by the precipitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 59 publications
(102 reference statements)
2
46
0
Order By: Relevance
“…On annual to decadal timescales, many modern stalagmite δ 18 O records show significant negative correlations with local instrumental EASM or annual precipitation amount for the last 200 years [44,62,63,128,150,178,199,200]. However, there exists a mismatch between speleothem δ 18 O and mean annual rainfall in the south region of the EASM area [54,201]. It has been argued that speleothem δ 18 O changes over the EASM region reflect variations in the ratio of water vapor sourced from the 18 O-depleted Indian Ocean to the nearby 18 O-enriched Western Pacific Ocean-the so-called "circulation effect"-which appears to be controlled by the El Niño-Southern Oscillation (ENSO) cycle [202][203][204].…”
Section: Significance Of Speleothem δ 18 O As a Climate Proxy In The mentioning
confidence: 99%
See 4 more Smart Citations
“…On annual to decadal timescales, many modern stalagmite δ 18 O records show significant negative correlations with local instrumental EASM or annual precipitation amount for the last 200 years [44,62,63,128,150,178,199,200]. However, there exists a mismatch between speleothem δ 18 O and mean annual rainfall in the south region of the EASM area [54,201]. It has been argued that speleothem δ 18 O changes over the EASM region reflect variations in the ratio of water vapor sourced from the 18 O-depleted Indian Ocean to the nearby 18 O-enriched Western Pacific Ocean-the so-called "circulation effect"-which appears to be controlled by the El Niño-Southern Oscillation (ENSO) cycle [202][203][204].…”
Section: Significance Of Speleothem δ 18 O As a Climate Proxy In The mentioning
confidence: 99%
“…Baker et al (2015) [192] suggested that the atmospheric moisture pathway might significantly influence precipitation and speleothem δ 18 O in the monsoonal China. In SE China, especially in the region of "spring persistent rain", speleothem δ 18 O variability seems to be controlled primarily by the seasonality of rainfall (i.e., the ratio of EASM precipitation versus that from the remaining seasons), which is modulated by ENSO on annual to decadal timescales [54,205]. Furthermore, the "circulation effect" may play an important role in Central China, where the ISM and the EASM dominate alternatively on annual to multidecadal scales, depending on the position/strength of the Western Pacific Subtropical High (WPSH) [50].…”
Section: Significance Of Speleothem δ 18 O As a Climate Proxy In The mentioning
confidence: 99%
See 3 more Smart Citations